2014
DOI: 10.1016/j.celrep.2014.09.022
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Tissue-wide Synchronization of Mitochondrial Metabolic Oscillations

Abstract: Summary Little is known about the spatio-temporal coordination of mitochondrial metabolism in multicellular organisms in situ. Using intravital microscopy in live animals, we here report that mitochondrial metabolism undergoes rapid and periodic oscillations under basal conditions. Notably, mitochondria in vivo behave as a network of functionally coupled oscillators, which maintain a high level of coordination throughout the tissue via the activity of gap junctions. These findings reveal a unique aspect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 47 publications
4
35
0
Order By: Relevance
“…It is also worth mentioning that recently metabolic oscillations in cells with a period of approximately 10 to 12 s, were measured in vivo [102] which is many orders of magnitude slower than any AC electric field effects discussed here. Hence, it is safe to assume that there is a very unlikely possibility of electric field effects in the 100 kHz range to interfere with cellular metabolism.…”
Section: Ac Electric Field Effects On Subcellular Structuresmentioning
confidence: 88%
“…It is also worth mentioning that recently metabolic oscillations in cells with a period of approximately 10 to 12 s, were measured in vivo [102] which is many orders of magnitude slower than any AC electric field effects discussed here. Hence, it is safe to assume that there is a very unlikely possibility of electric field effects in the 100 kHz range to interfere with cellular metabolism.…”
Section: Ac Electric Field Effects On Subcellular Structuresmentioning
confidence: 88%
“…Reactive oxygen species (Aon et al , 2004) and gap junctions (Porat-Shliom et al , 2014) control the synchronization of mitochondrial activity, the oscillations were confirmed by intravital microscopy in living animals (Porat-Shliom et al , 2014) These oscillations were found to disappear with interruption of circulation, inhibiting complex I, and by scavenging ROS. However, they persist but are not coordinated when carbenoxolone, a gap junction inhibitor, is administered.…”
Section: The Mitochondrial Theory Of Agingmentioning
confidence: 89%
“…Recent reports have suggested that mitochondria undergo rapid and constitutive metabolic oscillations in a coordinated manner in individual cells as well as in supracellular networks in the tissue (Porat-Shliom et al , 2014). Reactive oxygen species (Aon et al , 2004) and gap junctions (Porat-Shliom et al , 2014) control the synchronization of mitochondrial activity, the oscillations were confirmed by intravital microscopy in living animals (Porat-Shliom et al , 2014) These oscillations were found to disappear with interruption of circulation, inhibiting complex I, and by scavenging ROS.…”
Section: The Mitochondrial Theory Of Agingmentioning
confidence: 99%
“…This could be accomplished by extending our method from the organ level to the cellular level to visualize local Ca 2þ responses. Subcellular events in salivary acinar cells, including membrane trafficking, cytoskeletal organization, and mitochondrial metabolism, were visualized successfully by the Weigert group, using confocal and two-photon microscopy [52][53][54]. These methods might be applicable for visualizing subcellular Ca 2þ responses in live animals.…”
Section: Prospectivementioning
confidence: 98%